Representasi Perempuan Mandiri dalam Iklan Tolak Angin Ditinjau dari Analisis Wacana Kritis Norman Fairclough - Octavianti, Dinda Sekar (Research Community for Critical Society and Environment, 2024)
The development of women's roles in various aspects of life has begun, including in Indonesia. In the modern era, many women pursue higher education and earn academic degrees, allowing them to be involved in various professions and industries. In addition, women in Indonesia are increasingly actively participating in the world of work. This research paper applies the three-dimensional critical discourse analysis theory proposed by (Fairclough, 1992), which views texts, in this case advertisements, based on three dimensions. The three dimensions include (1) textual dimensions (microstructural), (2) discursive practice dimensions (mesostructural), and (3) sociocultural practice dimensions (macrostructural). The data in this study are in the form of speech in the Tolak Angin commercial advertisement broadcast on October 31, 2023, via the Tolak Angin YouTube channel television with the advertisement title